2004
DOI: 10.1038/sj.ejcn.1601791
|View full text |Cite
|
Sign up to set email alerts
|

Growth and feeding practices of Vietnamese infants in Australia

Abstract: Objective: To investigate the growth and feeding practices in first-generation Vietnamese infants living in Australia. Design: Cohort study. Setting: The study was conducted between 1999 and 2002 in Sydney. Subjects: A total of 239 Vietnamese women were recruited randomly from antenatal clinics, and of these 210 were initially seen. During the first year, 20 cases (9.5%) were lost to follow-up. Data were collected at 0.5, 2, 4, 6, 9 and 12 months. Results: Vietnamese infants were significantly longer and heavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…However, the evidence provided here cannot be deemed conclusive, because the genetic pool of Indians who migrated to the UK does not necessarily coincide with that of others who remain in India. At the same time, this paper contributes to a literature that show how individuals that migrate from poor to developed countries are usually characterized by better growth patterns than their same-ethnicity counterparts who do not migrate (Yip et al 1992, Duggan and Harbottle 1996, Mei et al 1998, Smith et al 2003Nguyen et al 2004 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the evidence provided here cannot be deemed conclusive, because the genetic pool of Indians who migrated to the UK does not necessarily coincide with that of others who remain in India. At the same time, this paper contributes to a literature that show how individuals that migrate from poor to developed countries are usually characterized by better growth patterns than their same-ethnicity counterparts who do not migrate (Yip et al 1992, Duggan and Harbottle 1996, Mei et al 1998, Smith et al 2003Nguyen et al 2004 …”
Section: Discussionmentioning
confidence: 95%
“…Yip et al (1992) and Mei et al (1998) study the growth patterns of children of Asian refugees in the United States, and conclude that factors such as diet and health services, rather than genetic factors, explain most of the inter-country variation in child anthropometric indices. Nguyen et al (2004) show that growth patterns of Vietnamese infants who reside in Australia are close to the U.S. reference charts, despite their parents' anthropometric indices being below reference. Gjerdingen et al (1996) find, instead, that a sample of 0 to 5-year old children of Hmong ethnicity living in the United States were slightly heavier then the CDC-WHO77 reference mean for the first months after birth, and shorter thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…6 Colostrum is typically not offered, but discarded, as it is thought to be unhealthy for the baby. 9 Nguyen et al 8 first documented in 2004 that 78.6% of Vietnamese Australians initiated breastfeeding within the first 3 days after birth and gave their infant colostrum. McLachlan et al 30 recently reported breastfeeding initiation rates at 75% amongst 100 Vietnamese Australians, with 64.9% of women reporting colostrum to be as healthy as formula.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,7 However, after immigrating to Western countries, many are offered infant formula instead of breast milk. 8,9,10 Many women who breastfed their Vietnamese born infants do not breastfeed their Western-born infants. 9,10,11 Ghaemi-Ahmadi reported high breastfeeding and duration rates in Vietnam (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation